2013
DOI: 10.1177/0741932513485448
|View full text |Cite
|
Sign up to set email alerts
|

Does Access Matter? Time in General Education and Achievement for Students With Disabilities

Abstract: This study examined the relationship between hours in general education and achievement in reading and mathematics for students with disabilities. The study population included more than 1,300 students between the ages of 6 and 9 years old within 180 school districts. Hierarchical linear modeling (HLM) was utilized with the Pre-Elementary Education Longitudinal Study (PEELS) data set (Institute of Education Sciences). The relationship between hours in general education and achievement in reading and mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 19 publications
2
58
0
2
Order By: Relevance
“…Evidence also indicates that students with and without disabilities who are educated in inclusive classrooms have better academic outcomes than students who are educated in noninclusive classrooms. For example, several studies have shown that students without disabilities make significantly greater progress in reading and math when taught in an inclusive setting with students with disabilities (Cole, Waldron, & Majd, 2004;Cosier, Causton-Theoharis, & Theoharis, 2013).…”
Section: Myth 1 Inclusive Education Will Have a Negative Impact On Smentioning
confidence: 99%
“…Evidence also indicates that students with and without disabilities who are educated in inclusive classrooms have better academic outcomes than students who are educated in noninclusive classrooms. For example, several studies have shown that students without disabilities make significantly greater progress in reading and math when taught in an inclusive setting with students with disabilities (Cole, Waldron, & Majd, 2004;Cosier, Causton-Theoharis, & Theoharis, 2013).…”
Section: Myth 1 Inclusive Education Will Have a Negative Impact On Smentioning
confidence: 99%
“…The findings from the current investigation provide the first national picture of the possible factors that might explain placement of students with multiple disabilities in general education classrooms. The present study extends the work of previous researchers (Cosier and Causton-Theoharis, 2011;Cosier, Causton-Theoharis and Theoharis, 2013;Fisher and Meyer, 2002;Szumski and Karwoski, 2012) by (1) examining a large and varied number of variables supported by literature to explain placement decisions that have implications for educational practice and (2) utilising a large, nationally representative sample size (usually a challenge when investigating any phenomenon for students with low-incidence disabilities).…”
Section: Discussionmentioning
confidence: 58%
“…Finally, inclusive education results in many positive outcomes for all students, including enhanced social skills (Cosier, Causton‐Theoharis, & Theoharis, ). However, rates of inclusion diminish as students reach high school (Hanson, ), resulting in many students entering PSEs lacking social and emotional skills needed to appropriately navigate complex college relationships.…”
Section: Lessons Learned and Future Directionsmentioning
confidence: 99%